How does the development of the digital economy in RCEP member countries affect China's cross-border e-commerce exports? - Dong Wang; Peiyuan Xu; Bowen An; Yingying Song (PLoS ONE)
As a significant new mode of trade export in the digital economy era, cross-border e-commerce injects new momentum into trade cooperation among the Regional Comprehensive Economic Partnership (RCEP) member countries. This paper utilizes multi-dimensional panel data constructed from World Bank databases and UNCTAD databases from 2012 to 2021 to analyze the impact mechanism of RCEP member countries' digital economy development on China's cross-border e-commerce export through direct and indirect channels and conducts empirical tests on it. The research results show that, in terms of direct impact, the development of the digital economy in RCEP member countries has promoted China's cross-border e-commerce export, and its impact is heterogeneous. Regarding indirect impact, improving the quality of RCEP member countries' transportation infrastructure and institutional quality is a moderating factor promoting China's cross-border e-commerce export. This study provides important insights for deepening the development of the digital economy in RCEP countries and promoting China's cross-border e-commerce export.